You are on page 1of 12

DERIVATIVES OF ALGEBRAIC FUNCTIONS Theorems on Differentiation of Algebraic Functions And Higher-Order Derivatives

Theorem 1: If c is constant and if f(x) = c for all x, then f (x) = 0 The derivative of a constant is always ZERO. Theorem 2: THE POWER RULE If n is a positive integer and f(x) = xn, then f (x) = nxn-1 if n is negative: Theorem 3 The derivative of constant times a function is the constant times the derivative of a function. f (x) = -nx-n-1

De c f(x) = c De f(x) Theorem 4 The derivative of the sum of two functions is the sum of their derivatives if these derivatives exist. Dx [f(x) + g(x)] = Dx f(x) + Dx g(x) Theorem 5 The derivative of the sum of a finite number of functions is equal to the sum of their derivatives if these derivatives exist. Theorem 6 THE PRODUCT RULE

The derivative of the product of the two functions is equal to the first function times the derivative of the second plus the second function times the derivative of the first. Dx [f(x) g(x)] = f(x) Dx g(x) + g(x) Dx f(x) Theorem 7 THE QUOTIENT RULE The derivative of the quotient of the two functions is the fraction having its denominator, the square of its original denominator, and its

numerator as its denominator times the derivative of the numerator minus the numerator times the derivative of the denominator.

Dx

[ ]=

Exercise: Find what is needed: 1. y = 5x4 + 3x3 +2x 2. y = 4x3 - x2 + 5 3. y = (x2-1)2 4. x = 5. w = 6x3 + 4x2 +10x 6. y = 3x5 + 4x4 +3x3 +10x2 + 5x find y find y find y find x find w find y

Derivative of a Composite Function and the Chain Rule  To find the derivative of a composite function, we apply the chain rule, one of the important computational theorems in Calculus. Theorem 1: CHAIN RULE

If f and g are two functions defined by y = f(u) and u = g(x) respectively then a function defined by y = f [g(x)] or fog(x) is called a composite function or a function of a function.

(f o g) (x) = f (g(x)) g (x)

If y is a differentiable function of u and x is a differentiable function then,

Example:

If y= (2x3 4)3 find

Solution: Let u = (2x3 4) so that y=u3

then

= 3u2

and

= 6x2

using Theorem 1:

=3u2 6x2
= 3(2x3 4)2 (6x2) = 18x2(2x3 4)2 Exercise: Find the derivative following equations using the Derivative of a Composite Function and the Chain Rule: 1. y = ( )

2. y = (2x3+x4)(x3+3) 3. y =

4. If g=(2x3-4)3, find 5. If y = 6t2+2t-1 and x = t3-1, find 6. If x = y3-2y+1, find

Implicit Differentiation In calculus, a method called implicit differentiation makes use of the chain rule to differentiate implicitly defined functions.

 If y is a function of x but y cannot be expressed in terms of x explicitly, we can still find by implicit differentiation. Given an equation

relating y and x, we differentiate both sides of the equation and solve for by simple algebraic manipulation.

Example:

If y is a function of x such that y3 = x 2, find

Solution: Differentiating, with respect to x both sides of y3 = x 2 keeping in mind that y is a function, we get:

3y2

=1

Exercise: Find the implicit differentiation of the following: 1. 8x2+y2=10 2. 4x3 2y3 = x 3. sin2 (3y) = x + y + 1 4. cos ( x y) = y cos (x) 5. Assume that y is a function of x . Find y' = dy/dx for x3 + y3 = 4 . 6. Assume that y is a function of x . Find y' = dy/dx for x3 + y3 = 4 .

Differentiation of Trigonometric Functions  The differentiation of trigonometric functions is the mathematical process of finding the rate at which a trigonometric function changes with respect to a variable--the derivative of the trigonometric function. Commonplace trigonometric functions include sin(x), cos(x) and tan(x). For example, in differentiating f(x) = sin(x), one is calculating a function f (x) which computes the rate of change of sin(x) at a particular point a. The value of the rate of change at a is thus given by f (a). Knowledge of differentiation from first principles

is required, along with competence in the use of trigonometric identities and limits. All functions involve the arbitrary variable x, with all differentiation performed with respect to x. Nomenclature:

=1

=0

Table 1: The 6 Trigonometric Functions and their derivatives

y=sin(x) y=cos(x) y=tan(x) y=cot(x) y=sec(x) y=csc(x)

y =cos(x) dx y =-sin(x) dx y =sec2(x) dx y =-csc2(x) dx y =sec(x)tan(x) y =-csc(x)cot(x)

Examples:

1.

y = sin3x y = cos3x (3) y = 3cos 3x

2. w = tan 2 w = sec2 2 (2) w = 2sec2 2

3. v = csc 7 v = -csc 7 cot 7 (7) v = -7 csc 7 cot 7

Differentiation of Inverse Trigonometric Functions In mathematics, the inverse trigonometric functions (occasionally called cyclometric functions) are the inverse functions of the trigonometric functions with suitably restricted domains . The notations sin 1, cos 1, etc. are often used for arcsin, arccos, etc., but this convention logically conflicts with the common semantics for expressions like sin2(x), which refer to numeric power rather than function composition,

and therefore may result in confusion between multiplicative inverse andcompositional inverse. The following derivatives are found by setting a variable y equal to the inverse trigonometric function that we wish to take the derivative of. Using implicit differentiation and then solving for inverse function is found in terms of y. To convert , the derivative of the back into being in terms

of x, we can draw a reference triangle on the unit circle, letting be y. Using the Pythagorean theorem and the definition of the regular trigonometric functions, we can finally express in terms of x.

Table 2: The 6 Inverse Trigonometric Functions and their derivatives

(Arc sin u)=

(Arc cos u)=

(Arc cos u)=

(Arc sec u)=

(Arc tan u)=

(Arc cot u)=

Example:

1.

y= Arc sin 3x

Let u = 3x du = 3

u2 = 9x2

Answer:

y=

2. Let u = t2 du = 2t

y = Arc tan (t2)

u 2 = t4

Answer:

y =

3. Let u = 4t du = 4

y = Arc cos 4t

u2 = 16t2

Answer:

y =

Exercise: Find the derivative of the following: 1. x = cos4t 2. u = tan3 3. w = sin9x 4. v = sec y 5. x = tan ( 6. y = cos3 5x

- y)